Pengujian Efek Hipoglikemik Fraksi Petroleum Eter dan Etil Asetat Daun Dandang Gendis (Clinacanthus nutans (Burm. F.) Lindau) - Junius Gian Ginting (Herbal Medicine Journal, 2022)
The investigation had been done about hypoglycaemic effect from Clinachanthus nutans (Burm f.) Lindau extract, which in petroleum ether extract and ethyl acetate extract, that used Glucose Method Tolerance for Mice. The extract of Clinachanthus nutans (Burm f.) Lindau leave was carried out by masseration and using ethanol 80% as solvent, and gradually fractination for ethanol extract with petroleum ether and ethyl acetate solvent. Further, the glucose tolerance had been done for petroleum ether fraction and ethyl acetate. The mice was fasting during 17 hours and the blood glucose level and weight of mice was measured and given the 50% glucose liquid with dose 4 mg/kg bw. After 30 minutes the blood glucose level can be measure again. Divided the mice to 6 group, Group I: control (CMC 0,5% dose 1 % bw); Group II until Group V given the petroleum ether fraction and ethyl acetate fraction with dose 15, 30, 45 dan 60 mg/kg bw; Group VI: given the Glibenclamid suspension dose 1 mg/kg bw as equal. Fixed blood glucose level of mice after 60, 90, 120, 150 and 180 minutes to have use of glucometer (EZ Smart). The result showed that petroleum ether extract doesn’t have hypoglycaemic effect, but in dose 45 and 60 mg/kg bw has given hypoglycaemic effect which to get near Glibenclamid suspension in dose 1 mg/ kg bw with blood glucose level decrease 0,05 (ɑ=0,05).